Sistem Pemantauan Kondisi Tanah Sawah Padi Berbasis Wireless Sensor Network - Emansa Hasri Putra; Mochammad Susantok; Qurratul Aini (UIN Sultan Syarif Kasim Riau, 2015)
Rich soil in nutrients and has sufficient organic content, greatly affects the growth and development of rice plants that grow optimally. However, it is not easy to create the ideal conditions of the soil for rice plants. For that farmers need to know what variables that influence these ideal conditions. The easiest way to find out is by measuring variables pH, humidity, and temperature of the rice paddy soil conditions. Condition monitoring systems made of rice paddy field aims to help farmers get information measuring pH, humidity, and temperature of the rice paddy soil conditions. Paddy soil condition monitoring system based on wireless sensor network paddy using four sensor nodes has been successfully tested at the site of ground rice fields in Pelalawan. Server monitoring the rice paddy soil conditions, has also succeeded in showing the results of measurements of pH, temperature, and soil moisture of four sensor nodes.Keywords: network, rice, sensor, soil, wireless